Assessment of treatment outcomes and associated factors among patients treated with clozapine at amanuel mental specialized hospital, Addis Ababa, Ethiopia - Zehara Reshid; Kibrom Haile; Getinet Ayano; Alem Kebede; Aynalem Biru; Zegeye Yohannis (PLoS ONE, 2025)
Background Clozapine is a medication used in psychiatry. It is the first atypical antipsychotic drug and the most effective in treatment resistant cases of schizophrenia and schizoaffective disorder. Studies also show benefits of clozapine in patients with tardive dyskinesia. However, there is scarcity of studies which show the outcome of clozapine treatment and factors associated with it in the Ethiopian context. Objective The aim of the study was to assess treatment outcome and factors associated with it among patients treated with clozapine at Amanuel Mental Specialized Hospital Addis Ababa, Ethiopia. Method A hospital-based retrospective study, compounded by cross-sectional design was conducted from June 1–30, 2022. A total of 71 clozapine treated patients were taken through census method. An interviewer administered structured questionnaire, retrospective data from patient medical records, and clinical evaluation of severity and improvement (CGI) were used to collect data. The collected data were entered into Epidata version 4.6 Software then exported to the Statistical Package for the Social Sciences (SPSS) version 25 for statistical analysis. Bivariable and multivariable logistic regression analyses were used to identify factors associated with treatment outcomes. P-values less than 0.05 were considered statistically significant and strength of the associations were presented by adjusted odds ratios with 95% confidence intervals. Results Fifty one (71.8%) of participants showed improvement by clozapine treatment. Literacy level of high school and above showed significant positive association with treatment outcome (AOR: 7.65, 95% CI: 1.26–46.36, p<0.05) while extreme severity of illness at onset of clozapine treatment showed significant negative association with treatment outcomes (AOR: 0.13, 95% CI: 0.02–0.99, p<0.05). Conclusions Treatment with clozapine resulted in significant improvement in clinical and functional outcomes of treatment-resistant schizophrenia and schizoaffective disorder, as well as in tardive dyskinesia. Higher literacy level and severity of illness at onset of treatment showed significant associations with outcome. Clozapine is an atypical or second generation antipsychotic first used in the 1960s. It was withdrawn at first after its use was associated with a number of deaths due to agranulocytosis in Finland in 1975 [1,2]. In 1988 a landmark study demonstrated that the medicine was helpful to patients with schizophrenia who were unresponsive to other medications. Clozapine was then reintroduced into clinical use [3]. Since then, clozapine has been shown to be the only medicine which reduced suicidal behavior in patients with schizophrenia. Clozapine is now the medicine of choice for treatment-resistant schizophrenia [1]. The antipsychotic efficacy and the complete absence of extrapyramidal adverse effects of clozapine have been well documented. The benefit of clozapine for treating patients with treatment-resistant schizophrenia and those who are particularly prone to extrapyramidal adverse effects has been most remarkable [2].